Analysis of Main Road Stability Due to The Effect of River Water Level Fluctuations and Rainfall (Case Study: Trengguli - Kudus Road Section) - Wijaya Kusuma, Akhdiat Fajar; Soemitro, Ria Asih Aryani; Warnana, Dwa Desa; Satrya, Trihandyo Rendy; Putra, Yanuar Dwi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
In Indonesia, many roads are built next to rivers due to several factors in terms of geography, topography, and function of the river. One of them is on the Trengguli - Kudus road where the road is flanked by two rivers. These road sections often experience damage in the form of cracks, potholes, and differential settlement. The existence of a river on the side of the road needs to be considered the possibility of the influence of changes in the river water level on the stability of the road. Rainfall also has a significant role in the stability of the main road considering that the rain that occurs is very intense, moreover, the road is already in cracked condition. This research was carried out numerically using the Plaxis program, with variations in river water level and rainfall adjusted to field conditions. The research results show that a rapid drawdown causes a significant decrease in the safety factor (SF=1.172). Even though the influence of rainfall is relatively small, it still reduces the safety factor (SF=1.152). The duration of the rapid drawdown only has a difference of <1.35%. However, the slope conditions are still within safe limits.